Estimation of the Rift Valley Fever burden of disease in the 2006/2007 outbreak in Kenya - Orinde, A.B.; Kimani, T.; Schelling, E.; Omolo, J.O.; Kikuvi, G.M.; Njenga, K.M. (International Livestock Research Institute, 2012)
Rift Valley Fever (RVF) virus causes severe epidemics in livestock and humans resulting in considerable economic losses from disruption of livestock production and market chain and morbidity and mortality in humans. This study estimated the burden of RVF disease in humans using disability adjusted life years (DALYs), assessed human health RVF epidemiological parameters and private and public health costs during the last RVF epidemic in the 2006/2007 in Kenya. We interviewed family members that cared for an infected person in eligible household and key informants in the public health sector in Garissa and Kilifi districts that were heavily affected by the epidemic and at the public health leaders at the national level to assess the private and public health costs. An eligible household was household that had an RVF cases during the 2006/2007 outbreak as identified from the linelist. Secondary data from the Ministry of Health and published literature were reviewed for epidemiological parameters including age and sex categorized incidences, proportions of disease manifestation, and mortality rates in order to compute DALYs using methods developed by the World Health Organization. A total of 127 eligible households were enrolled in to the study with one member interviewed in each household. Those interviewed in these households included 54% males and ranged from 19 to 81 years old with 40 and 45 years as mode and median age, respectively. The RVF virus predominantly infected males during the outbreak with an annual incidence of 0.7 per 1,000 population compared to females at 0.5 per 1,000 population. The burden of RVF during the 2006 and 2007 outbreak was 3.4 DALYs per 1000 population, representing 1% of the total DALYs and estimated household costs of USD120 for every human case reported. In comparison, the total burden of HIV/AIDS and malaria in Kenya is the highest at 24.2% and 7.2% DALYs, respectively. Our results provide vital data on burden of RVF for use by the Government and other institutions to guide in health policy making and resource allocations for prevention and control.